A qualitative exploration of weight management during COVID‐19. Issue 3 (22nd February 2022) - Thomson, Meigan; Martin, Anne; Long, Emily; Logue, Jennifer; Simpson, Sharon A.
Summary: COVID‐19 has been associated with worse outcomes in people living with obesity and has altered how people can engage with weight management. However, the impact of risk perceptions and changes to daily life on weight loss has not been explored. This study aimed to examine how COVID‐19 and perception of risk interacted with weight loss attempts in adults participating in a behavioural weight management programme. Forty‐eight participants completed a semi‐structured interview exploring the impact of COVID‐19 on their weight management experience. Interviews were completed via telephone and analysed using a thematic approach. Reaction to perceived risk varied, but most participants reported the knowledge of increased risk promoted anxiety and avoidance behaviours. Despite this, many reported it as a motivating factor for weight loss. Restrictions both helped (e.g., reduced temptation) and hindered their weight loss (e.g., less support). However, there was consensus that the changes to everyday life meant participants had more time to engage with and take control of their weight loss. To the authors' knowledge, this is the first study to explore the impact of COVID‐19 on participation in a weight management programme started during the pandemic in the United Kingdom. Restrictions had varying impacts on participant's weight loss. How risk is perceived and reported to participants is an important factor influencing engagement with weight management. The framing of health information needs to be considered carefully to encourage engagement with weight management to mitigate risk. Additionally, the impact of restrictions and personal well‐being are key considerations for weight management programmes.